2019
DOI: 10.1248/bpb.b18-00818
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Suppresses Growth of Breast Cancer by Targeting HMGB1 <i>in Vitro</i> and <i>in Vivo</i>

Abstract: Triptolide has been indicated potent anti-cancer effect involving multiple molecular targets and signaling pathways. High-mobility group box 1 (HMGB1) is a highly conserved DNA-binding protein taking part in breast cancer development. The therapeutic effect of triptolide on HMGB1 has not been reported. Thus, our study aims to clarify the role of HMGB1 in triptolide-induced anti-growth effect on breast cancer in vitro and in vivo. We demonstrated that triptolide significantly suppressed growth of breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…HMGB1 is reported to be highly expressed in many malignant tumours and is closely related to apoptosis, proliferation and migration of cancer cells [3,13]. Therefore, anticancer therapy targeting HMGB1 is attracting increased attention [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is reported to be highly expressed in many malignant tumours and is closely related to apoptosis, proliferation and migration of cancer cells [3,13]. Therefore, anticancer therapy targeting HMGB1 is attracting increased attention [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…TPL has been shown to have potent antitumor activity in various preclinical cancer models [8], such as lung cancer, breast cancer and pancreatic cancer [32][33][34]. However, the effect of TPL on MF was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been shown that HMGB1 can activate the TLR4/NF-kB signaling pathway, which promotes tumor cell proliferation, migration and invasion. 33 In addition, kang et al indicated that HMGB1 could induce the phosphorylation of p38 and JNK in leukemic cells. 34 Thus, we analyzed NF-kB p65, p38 and JNK, which are 3 key factors involved in tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%